Analisis Laporan Keuangan Berbasis Aplikasi Keuangan Digital Pada UMKM Keripik Syaha Kota Blitar - Elsa Nabella; Kevin Vansa Ernanda2; Emiliana Nisa Syahniar; Ircha Olifia; Mahendra Alfatoni Hadinata; Nanik Hariyana; , Dewi Deniaty Sholihah (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The development of industrial technology in this era made progress for the Indonesian economy. However, there are still some MSMEs that are still unable to take advantage of existing technological developments to regulate their business management, especially financial management. MSME actors in general do not pay much attention to recording detailed and clear financial statements. Therefore, this study is expected to be a reference for MSME actors in making financial reports. The purpose of this study is to provide an overview of the use of android-based digital financial applications for financial management, especially daily financial records with categories of sources of income and sources of expenditure. The method in the implementation is carried out in three methods, namely the approach method, the training method, and the mentoring method for Syaha Chips SMEs. This research was conducted to develop Syaha Chips SMEs in terms of financial management using digital financial applications.